Terreiro na avenida: relações entre o carnaval e as religiões afro-brasileiras em Passo Fundo/RS (2000 - 2015) - Candaten, Jeferson Sabino (2018)
In general, studies on Afro-Brazilian religions in Rio Grande do Sul understand the aforementioned religious field as a crossroads of three distinct paths, however, several meeting points can be seen throughout their trajectories, including Umbanda, the crusade (quimbanda) and batuque1. These are the main religions inherited from African origins in this State which, in the last IBGE Demographic Census, showed itself to be more religiously Afro-Brazilian than any other in Brazil2. The idea of ​​an insignificant number of enslaved labor in Rio Grande do Sul, especially in the northern region of the state, is a thesis that cannot be sustained. This speech amplifies the strident noise of the currents of yesteryear that still today does not allow us to recognize the contribution of enslaved African and Afro-descendant populations to the history of Rio Grande do Sul3. However, studies on Afro-Brazilian religions, samba, Carnival and other aspects of Afro-Rio Grande culture have been darkening our eyes so that we can finally see reality as it really is.